Novel MCA/ID syndrome with ASH1L mutation. Issue 6 (10th April 2017) - Okamoto, Nobuhiko; Miya, Fuyuki; Tsunoda, Tatsuhiko; Kato, Mitsuhiro; Saitoh, Shinji; Yamasaki, Mami; Kanemura, Yonehiro; Kosaki, Kenjiro
Abstract : We identified a novel mutation in ASH1L in a patient with severe intellectual disability, growth failure, microcephaly, facial dysmorphism, myelination delay, and skeletal abnormalities. ASH1L is a histone methyltransferase that associates with the transcribed region of all active genes examined, including Hox genes. It catalyzes H3K36 methylation and plays important roles in development. There has been increasing evidence that heterozygous mutation of ASH1L is associated with ID and autism spectrum disorders. We suggest that ASH1L abnormalities may cause a novel MCA/ID syndrome.